2014
DOI: 10.1111/apa.12756
|View full text |Cite
|
Sign up to set email alerts
|

Independence does not come with the method – treatment of neurogenic bowel dysfunction in children with myelomeningocele

Abstract: TAI and ACE are effective treatments, but time-consuming and difficult to perform independently. Higher parental satisfaction is obtained with ACE. Irrespective of method the children who can use the toilet independently report a higher quality of life, which makes efforts to support independence valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 30 publications
5
25
0
11
Order By: Relevance
“…Other studies have reported that hydrocephalus and Chiari II malformation are present in the majority of children with open NTDs , with the occurrence of severe brainstem dysfunction and subsequent need for surgical decompression in 4–8.8% . Cognitive difficulties have been described in children with open NTDs both in regard to low IQ and the need for assistance with schoolwork . Previous research has pointed to the associated presence of hydrocephalus as an explanation , which is in agreement with our data.…”
Section: Clinical Features According To Diagnosissupporting
confidence: 92%
See 3 more Smart Citations
“…Other studies have reported that hydrocephalus and Chiari II malformation are present in the majority of children with open NTDs , with the occurrence of severe brainstem dysfunction and subsequent need for surgical decompression in 4–8.8% . Cognitive difficulties have been described in children with open NTDs both in regard to low IQ and the need for assistance with schoolwork . Previous research has pointed to the associated presence of hydrocephalus as an explanation , which is in agreement with our data.…”
Section: Clinical Features According To Diagnosissupporting
confidence: 92%
“…Achieving continence is a significant secondary aim. Clean intermittent catheterisation is the solution most frequently used for children with open NTDs or lipomatous malformations with bladder dysfunction . If bladder dysfunction is not a threat to kidney function, then surgery is postponed until the child is old enough to consent.…”
Section: Clinical Features According To Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The PedsQL child and parent formats were the most frequently used generic instruments in children. Nearly all of the studies that used the PedsQL found lower scores on all scales in the MMC children group as compared with the reference samples of healthy children (Oddson et al ; Abresch et al ; Flanagan et al ; Sumpter et al, ; Johansen et al ; Freeman et al ; Olesen et al ; Ramachandra et al ; Wide et al ; Murray et al ). The greatest reduction in HRQOL was found in physical functioning and the smallest one was in emotional functioning (Oddson et al ; Abresch et al, ; Sumpter et al ; Johansen et al ; Freeman et al ).…”
Section: Resultsmentioning
confidence: 98%